Pragmatic impacts of linguistic elision of noun and verb phrases in Saudi Business communication - Mohammad Awad Al-Dawoody Abdulaal (Studies in English Language and Education, 2026)
Although existing research has affirmed that omitting noun and verb phrases can streamline interactions and provide alternative interpretations for recipients, there is limited insight into how these elliptical constructions function in context in Saudi corporate settings. Therefore, this study investigates the interpretive utility of noun and verb phrase ellipsis in professional communication, aiming to uncover their role in enhancing discourse efficiency and interpretive emphasis. An exploratory sequential mixed research design was utilized, wherein a quantitative phase preceded and informed a qualitative interpretation phase. Both data strands were derived from 112 transcripts of corporate interactions, sampled systematically based on discourse type, encompassing meetings, negotiations, and training presentations sourced from official platforms and public archives. In the first phase, frequency analysis and chi-square testing identified patterns in the frequency and contextual use of elliptical structures. In the second phase, textual analysis examined how noun and verb phrases serve specific interactive goals such as comprehensibility, markedness, and persuasiveness, with qualitative interpretation building upon quantitative findings. Results revealed that noun and verb phrase ellipsis enhances communicative efficiency by reducing redundancy and directing attention toward important content. Noun phrases were effective in foregrounding key information, while verb phrases conveyed urgency and immediacy. Quantitative results further highlighted consistent structural patterns and their impact on emotional engagement. Additionally, strategic linguistic omission appeared to reinforce perceptions of speaker confidence and authority within corporate contexts. The study repositions linguistic omission not merely as a grammatical phenomenon but as a pragmatic strategy for directing attention and shaping interpretation through clarity and emphasis.